Konsep Diri Generasi Milenial Pelaku Minimalism Lifestyle - Azizah, Rahmalia Wulan (The Commercium, 2022)
Advances This study aims to find out how the millennial generation's self-concept who applies Minimalism Lifestyle uses a communication perspective by looking at how the Millennial Generation of Minimalism Lifestyle actors communicate themselves according to the theory of self-concept and symbolic interaction. This research is a descriptive qualitative research with phenomenological method. The paradigm used in this study is the constructivism paradigm where the researcher sees social conditions as a systematic analysis. Data collection was obtained from observation, in-depth interviews and documentation. The results of this study indicate that the internal factors in the formation of the self-concept of the millennial generation of Minimalism Lifestyle actors consisting of self-knowledge, self-expectations and self-evaluation are strongly influenced by the development of information technology. Likewise, external factors in the formation of the self-concept of the millennial generation of Minimalism Lifestyle actors, namely other people and reference groups are also influenced by the development of information technology where Minimalism Lifestyle actors are interconnected with each other in the virtual world. The self-concept that is formed is the characteristic of the self-concept living more functional, responsible, and open to new things. Keywords: Self concept, Minimalism Lifestyle, Millennial